Policy brief: Student mental health and wellbeing in Poland: Are the current policies and measures enough? - Bolor Jamiyandagva (Australian and New Zealand Journal of European Studies)
This policy brief addresses the critical state of student mental health and wellbeing in Poland. According to studies conducted by non-governmental and international organisations, the mental health and wellbeing of students in Poland have drastically worsened, necessitating immediate, nationwide and holistic action by all relevant authorities and stakeholders. The Polish Government has already taken some measures, such as joining the World Health Organisation (WHO) Mental Health Gap Action Programme in 2023, increasing the budget on child and adolescent mental health, and providing schools with psychologists to support students. However, significant challenges remain, including shortages of psychologists in schools, limited funding opportunities to schools, and a lack of comprehensive national policy or programs. This policy brief recommends the development of a national education policy and programs on student mental health and wellbeing that provides guidelines and framework for schools, educators, and other relevant education stakeholders.